An environmental history of the world [ humankind's changing role in the community of life - Hughes, J. Donald [ (Johnson Donald)] , 1932- (Routledge studies in physical geography and environment, 2009)
This book is an overview of human history in relationship to the natural environment, from origins to the present, with case studies of different societies in each period.